2022
DOI: 10.1177/08874034221112847
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Review of Hate Crime Legislation in the United States

Abstract: Hate-motivated crime remains problematic in the United States. California passed the first hate crime law in 1978; Congress followed in 1990. States continue to amend their hate crime legislation, producing an amalgam of statutory provisions. This article creates a conceptual framework from which to classify hate crime legislation across the 50 states and Washington, DC. Laws were identified through Westlaw. Analyses compared the types of crimes covered, discrete and insular minorities protected, prosecutorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Within this study, we focus on two broad types of violent victimization -hate crimes and gender-based violence, inclusive of stalking, sexual violence, and IPV. Persons with disabilities experience hate crimes and are a protected class in 29 states' hate crime statutes (Bills & Vaughn, 2022) albeit not in West Virginia. While very few incidents are classified as anti-disability in nature (less than 2%, FBI, 2022), Macdonald and colleagues' (2023) analysis of 33 case studies found that one's disability was central for many marginalized victims of hate crime and that disability may be overlooked when classifying these crimes.…”
Section: Victimization and Disabilitymentioning
confidence: 99%
“…Within this study, we focus on two broad types of violent victimization -hate crimes and gender-based violence, inclusive of stalking, sexual violence, and IPV. Persons with disabilities experience hate crimes and are a protected class in 29 states' hate crime statutes (Bills & Vaughn, 2022) albeit not in West Virginia. While very few incidents are classified as anti-disability in nature (less than 2%, FBI, 2022), Macdonald and colleagues' (2023) analysis of 33 case studies found that one's disability was central for many marginalized victims of hate crime and that disability may be overlooked when classifying these crimes.…”
Section: Victimization and Disabilitymentioning
confidence: 99%
“…Hate crimes are incidents that are committed in whole or in part due to a victim’s actual or perceived membership in a protected class (FBI, n.d.). There is variability across states in what protected classes are included in the respective statute, but most states provide protections based on animus toward the victim’s race, ethnicity, or religion ( N = 47; Bills & Vaughn, 2022). There is much more variability among states in offering protections for crimes that are anti-gender ( N = 29)/gender identity ( N = 12), anti-sexual orientation ( N = 33), or anti-disability ( N = 29; Bills & Vaughn, 2022).…”
Section: Hate Crimementioning
confidence: 99%
“…There is, however, considerable variation between individual states regarding which groups receive protection under hate crime laws. Some states recognize police and firefighters as protected classes, several recognize homelessness or political affiliation, whereas 17 states do not yet recognize sexual orientation, and 38 do not recognize gender identity as protected classes ( Bills & Vaughn, 2023 ).…”
mentioning
confidence: 99%